Penerapan Supply Chain Management di Cold Storage Turen - Dewi Masyitho; Lina Sriwahyuni; Fulan Mir'atul Maghfiroh; Yusuf Azwar Anas (Jurnal Pengabdian Masyarakat: Tipis Wiring, 2023)
This research was conducted to find out what the implementation of supply chain management is like in Cold Storage Turen, so that the benefits of implementing supply chain management in Cold Storage Turen will be seen. In this study using qualitative research methods, this type of research is included in the field research (field research). The type of data that we use in this study is primary data through observation and interview techniques and secondary data in the form of documentation. The data analysis method used in this study is a qualitative descriptive analysis method, namely collecting data, compiling data, presenting data, interpreting data, and drawing conclusions on the data that has been collected. The results of this study indicate that the flow of supply chain management carried out at Cold Storage Turen includes the planning, procurement, production, storage or warehousing, distribution and return stages. The benefits obtained by cold storage down from the supply chain management carried out are: being able to meet market demands, increasing company revenue, reducing unnecessary costs, timely delivery of products, avoiding stockouts, and growing the company.